Work system and work program evaluation on the performance of Lohjinawi Pringsewu Tile industry employees in 2022 - Wagiyo; Dewi Mariyam Widiniarsih; Nasyi'atun Inayati Utami; Purwanto (Enrichment : Journal of Management, 2023)
Performance is the result of work in quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities given to the person concerned, is there any influence of the work system and evaluation of work programs jointly on the performance of employees of the Lohjinawi Pringsewu Tile Industry employees in 2022. This research uses quantitative methods. Data collection uses observation, questionnaires, and documentation, with a total of 20 employees, all of whom are sampled. Data analysis used multiple linear regression with hypothesis testing using the t-test and f-test. The conclusion in this study is that there is an effect of the Work System and Evaluation of work programs jointly on employee performance in the Lohjinawi Pringsewu tile industry, as evidenced by the value of Fcount 17,405 > Ftable 3.55.